Infection phenotypes of a coevolving parasite are highly diverse, structured, and specific. (30th August 2021) - Fredericksen, Maridel; Ameline, Camille; Krebs, Michelle; Hüssy, Benjamin; Fields, Peter D.; Andras, Jason P.; Ebert, Dieter
Abstract: Understanding how diversity is maintained in natural populations is a major goal of evolutionary biology. In coevolving hosts and parasites, negative frequency‐dependent selection is one mechanism predicted to maintain genetic variation. While much is known about host diversity, parasite diversity remains understudied in coevolutionary research. Here, we survey natural diversity in a bacterial parasite by characterizing infection phenotypes for over 50 isolates in relation to 12 genotypes of their host, Daphnia magna . We find striking phenotypic variation among parasite isolates, and we discover the parasite can infect its host through at least five different attachment sites. Variation in attachment success at each site is explained to varying degrees by host and parasite genotypes. A spatial correlation analysis showed that infectivity of different isolates does not correlate with geographic distance, meaning isolates from widespread populations are equally able to infect the host. Overall, our results reveal that infection phenotypes of this parasite are highly diverse. Our results are consistent with the prediction that under Red Queen coevolutionary dynamics both the host and the parasite should show high genetic diversity for traits of functional importance in their interactions.